Search for new physics in mono-jet final states in pp collisions : at sqrt(s)=13 TeV with the ATLAS Experiment at the LHC /: at sqrt(s)=13 TeV with the ATLAS Experiment at the LHC. (2017) - Gustavino, Giuliano
No abstract available